El desempeño académico de los estudiantes de Décimo EGB en la materia de Estudios Sociales de la Unidad Camilo Gallegos Toledo durante el periodo 2022-2023 - Mendez Morocho, Jean Alexander (2024)
The main objective of this research is to analyze the academic performance of tenth-grade students of the "Camilo Gallegos Toledo" Educational Unit within the subject of Social Studies. During the research project, a mixed approach was used, where the information collected was given through student surveys and an interview with the teaching specialist, Mgs. Nancy Cardenas. The factors and reasons for the variability in academic performance will be described through the bibliographic compilation of social and psychological reasons for the interest or disinterest in the treated subject. The interview and survey tools used facilitated the obtaining of the analysis of the opinions of students and teachers, knowing, first of all, a discrepancy being a positive percentage of students who think that they have a regular to outstanding performance, while the teacher details because that are not positive and that on the contrary have a regular to lousy performance. In conclusion, education is the tool to progress and get ahead, but it is not only the teacher's job; it is equal work where the student's interest is reflected in their grades quantitatively and qualitatively.